Draft Annual Plan 1986-87 Volume II General Areas Government of Assam - Planning Commission (Planning Commission, 1986)
The Seventh plan allocation for Agriculture is fixed at Rs. 122.10 crores out of which a sum of Rs. 22.79 crores has been approved for the year 1985-86. Due to delay in finalising the 7th plan at the National level, the formulation of different sectoral Plan was also delayed. However, the programmes for Agricultural development has maintained the tempo and it is expected that the target will be fulfilled by the end of the current financial year.
Government of Assam, Planning and Development Department